Improvement in serological diagnosis of pertussis by external quality assessment. Issue 5 (16th April 2019) - Markey, Kevin; Douglas-Bardsley, Alex; Asokanathan, Cathy; Fry, Norman K.; Barkoff, Alex-Mikael; Bacci, Sabrina; Ködmön, Csaba; He, Qiushui
Abstract : Purpose. Serological analysis is an essential tool for the diagnosis of pertussis or whooping cough, disease surveillance and the evaluation of vaccine effectiveness against Bordetella pertussis . Accurate measurement of anti-pertussis toxin (anti-PT) IgG antibody levels in sera is essential. These measurements are usually performed using immunological methods such as ELISA and multiplex immunoassays. However, there are a large number of different assay systems available, and therefore standardization and harmonization between the methods are needed to obtain comparable data. Methodology. In collaboration with ECDC, the EUPert-LabNet network has organized three External Quality Assessment (EQA) schemes (2010, 2012 and 2016), which initially identified the diverse range of techniques and reagents being used throughout Europe. This manuscript discusses the findings of each of the EQA rounds and their impact on the participating laboratories. Results. The studies have shown an increasing number of laboratories (from 65% to 92%) using only the recommended coating antigen, purified PT, in immunoassays, as this allows exact quantification of serum anti-PT IgG and since PT is only produced by Bordetella pertussis this prevents cross-reactivity with other species. There has also been an increase in the numbers of laboratories (from 59% to 92%), including a WHO reference serum in their assays, which allows anti-PT IgG concentrations to be measured in International Units, thus enabling the comparison of results from different methods and laboratories. In addition, manufacturers have also considered these recommendations when they produce commercial ELISA kits. Conclusion. The three EQA rounds have resulted in greater harmonization in methods among different laboratories, showing a significant improvement of the ELISA methods used for serodiagnosis of pertussis.